Trends in laboratory testing for diabetes in Ontario, Canada 1995-2005: A population-based study - Lipscombe Lorraine L; Wilson Sarah E; Rosella Laura C; Manuel Douglas G (BMC, 2009)
Abstract Background There are concerns that testing for type 2 diabetes is low and many people with diabetes are not diagnosed. We sought to describe the rates of diabetes-related lab testing in Ontario from 1995-2005, among adults without diabetes, and to explore the extent to which the Canadian clinical practice guidelines for screening are being followed. Methods Descriptive counts of outpatient diabetes laboratory tests performed within Ontario's publicly funded, provincial health insurance program were recorded. The study population was Ontario residents, 20 years and older from 1995 to 2005 (9.3 million people in 2005). The Ontario Diabetes Database, a cumulative registry derived from administrative health records, was used to exclude people who had physician-diagnosed diabetes (n = 839,127 in 2005) from the primary analyses. Diabetes tests included serum blood glucose (SBG), hemoglobin A1c (HbA1c), and oral glucose tolerance tests (OGTT). Results In 2005, 37% of Ontario adults without pre-existing diabetes were tested with an SBG test, a 28% increase from 1995. The age-adjusted proportion of adults without diabetes undergoing a HbA1c test increased from 1.7% in 1995 to 6.0% in 2005. In 2005, a similar number of HbA1c tests were performed for individuals with diabetes (483,746) and without diabetes (496,616) despite large differences in the two groups' denominators. Less than 1% of Ontarians underwent OGTT testing in any year between 1995-2005. Nearly two-thirds of adults age 40 years and over had an SBG test over a 3-year period (April 1, 2002-March 31, 2005), in accordance with the Canadian Diabetes Association recommendations. Conclusion Diabetes testing is common and has increased over the last ten years. Despite its absence in Canada's diabetes screening recommendations, HbA1c testing among individuals without diabetes is increasing rapidly, and OGTT, which is recommended, is rarely performed.